Онлайн опитування студентів у системі забезпечення якості вищої освіти - Мороз, Володимир Михайлович; Садковий, Володимир Петрович; Бабаєв, Володимир Миколайович; Мороз, Світлана Анатоліївна (My University, 2018)
За результатами аналізу світового досвіду щодо участі студентів в оцінюванні забезпечення закладами вищої освіти якості освітньої діяльності та якості вищої освіти в цілому обґрунтовано можливість включення студентів до експертних груп з моніторингу якості вищої освіти. Розглянуто історію імплементації інструментарію анкетування студентів до механізмів моніторингу якості вищої освіти та проведено порівняльний аналіз вітчизняного досвіду залучення студентів до оцінювання її якості з відповідним закордонним досвідом. Визначено особливості організації та проведення опитування студентів у межах міжнародного консорціуму "Student experience in the research university" та розглянуто перспективи використання інструментарію онлайн опитування в системі контролю якості вищої освіти, а також рівня професійної діяльності університетів. Наведено вимоги до програмного продукту, використання якого експертом з оцінювання якості вищої освіти може забезпечити ефективність онлайн опитування студентів та гарантоване досягнення мети відповідного моніторингу. Виявлено переваги і недоліки онлайн опитування студентів як інструменту моніторингу якості вищої освіти. Доведено переваги використання організатором опитування хмарних сервісів для розбудови анкети опитування студентів та аналізу отриманих відповідей. Сформульовано висновки щодо можливості використання онлайн опитування студентів у системі забезпечення якості вищої освіти як на університетському, так і на державному рівнях, а також обґрунтовано практичні рекомендації за напрямом використання інструментарію анкетування студентів у межах механізмів контролю його якості. Визначено напрями подальших наукових пошуків щодо розвитку проблематики використання хмарних технологій для оцінювання рівня забезпечення закладами вищої освіти якості освітньої діяльності та якості вищої освіти.

Based on the results of the analysis of world experience on the participation of higher education graduates in assessing the quality of educational activities of higher education institutions and the quality of higher education in general, the possibility of including students in expert groups for monitoring the quality of higher education has been substantiated. There was considered the history of implementation the toolkit for surveying the students into the mechanisms of monitoring the higher education quality. Comparative analysis of the domestic experience on attracting the higher education graduates to the assessment of higher education quality with the relevant foreign experience has been conducted. The peculiarities of the organization and conducting of students surveys within the framework of the international consortium "Student experience in the research university" are determined. The authors have considered the prospects of use of the online survey toolkit for the quality control system in higher education, as well as the level of professional activity of universities. The requirements for a software product, that the expert in assessing the quality of higher education can use to ensure the effectiveness of online surveys of students and the guaranteed achievement of the goal of appropriate monitoring are given. The advantages and disadvantages of online surveys of students as a tool for monitoring the quality of higher education have been identified. The benefits of using the cloud service survey by the organizer for development of the questionnaire for students surveys and analysis of the received answers have been proved. In addition, the paper provides conclusions on the possibility of using the online survey of students in the system for quality assurance in higher education both at university and at the state level, as well as practical recommendations on the use of questionnaires for higher education applicants in the framework of mechanisms for monitoring its quality. The directions of further scientific researches concerning the development and using cloud technologies for assessing the level of quality assurance in higher education institutions, the quality of educational activities and higher education as a whole have been formulated.
Online survey of students in the system for quality assurance in higher education
Keywords: інформаційне середовище; освітні послуги; хмарні технології; програмні продукти; higher education quality; institutions of higher education; online student survey; cloud technologies